2004
DOI: 10.2307/3473442
|View full text |Cite
|
Sign up to set email alerts
|

Convergence, Divergence, and Homogenization in the Ecological Structure of Emydid Turtle Communities: The Effects of Phylogeny and Dispersal

Abstract: Studies that have explored the origins of patterns of community structure from a phylogenetic perspective have generally found either convergence (similarity) in community structure between regions through adaptive evolution or lack of convergence (dissimilarity) due to phylogenetic conservatism in the divergent ecological characteristics of lineages inhabiting different regions. We used a phylogenetic approach to document a third pattern in the structure of emydid turtle communities. Emydid communities in sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Associations between biogeographic history and largescale climatic or macrohabitat preferences have been observed in plants in the Valerianaceae 8 and in Emydid turtles 9 . In contrast, the hydraulic niches that characterize Psychotria and Palicourea with a common centre of origin differentiate species on a scale of only a few metres in the forest understory 19 , and therefore bring biogeographic assembly into a spatiotemporal scale that is commensurate with competition and ecological coexistence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations between biogeographic history and largescale climatic or macrohabitat preferences have been observed in plants in the Valerianaceae 8 and in Emydid turtles 9 . In contrast, the hydraulic niches that characterize Psychotria and Palicourea with a common centre of origin differentiate species on a scale of only a few metres in the forest understory 19 , and therefore bring biogeographic assembly into a spatiotemporal scale that is commensurate with competition and ecological coexistence.…”
Section: Discussionmentioning
confidence: 99%
“…the tropical conservatism hypothesis) 1 and the recent radiation of cold-adapted Laurasian, even Himalayan, plant lineages in the Andean cordilleras 8 . Niche conservatism might also allow geographic history to influence the assembly of ecological communities over shorter time periods and at finer spatial scales [9][10][11] if the habitat affinities of species comprising contemporary ecological communities are similar to ancestral ecological niches that evolved in response to environments experienced elsewhere.…”
mentioning
confidence: 99%
“…For example, Stephens and Wiens (2004) sought to explain the geographical distribution of emydid turtles in eastern North America, which exhibit two broad patterns of community structure. Phylogenetic analyses of morphological and molecular data combined with details of habitat and diet revealed that the differences between the two groups are predominantly owing to "phylogenetic conservatism" (i.e., descent from two distinct evolutionary lineages), although the dispersal of several species from one group to the other has reduced these differences.…”
Section: Biogeographymentioning
confidence: 99%
“…25). For example, it has long been assumed, and sometimes demonstrated, that within a habitat type, the amount of ecological differentiation among species is proportional to the amount of evolutionary and genetic divergence (26). Ecological differentiation can result in reduced resource use overlap between species, allowing species to stably coexist together (e.g., niche partitioning).…”
mentioning
confidence: 99%